2021
DOI: 10.7196/samj.2021.v111i8.15496
|View full text |Cite
|
Sign up to set email alerts
|

Quality and turnaround times of viral load monitoring under prevention of mother-to-child transmission of HIV Option B+ in six South African districts with a high antenatal HIV burden

Abstract: Considering the scarcity of information around the third 90 for antenatal and postnatal clients, we sought to understand two aspects of routine VL monitoring in high antenatal HIV prevalence districts This open-access article is distributed under Creative Commons licence CC-BY-NC 4.0.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Client-related barriers and long turnaround times for availability of VL results are examples of long-standing challenges that interfere with retention in care and timely follow-up management of VL and ART in LMIC settings 7 32–35. In a 2018 evaluation of this district and five others, for example, we found that on average at district-level, between 37% and 100% of clinics delay (>7 days) returning VL results to PMTCT clients after the clinic has received them from the laboratory 36. Given that the most cited potential barrier to ART adherence in this current study was time inconvenience, we hypothesise that this factor contributed to women delaying clinic attendance for their follow-up visits.…”
Section: Discussionmentioning
confidence: 88%
“…Client-related barriers and long turnaround times for availability of VL results are examples of long-standing challenges that interfere with retention in care and timely follow-up management of VL and ART in LMIC settings 7 32–35. In a 2018 evaluation of this district and five others, for example, we found that on average at district-level, between 37% and 100% of clinics delay (>7 days) returning VL results to PMTCT clients after the clinic has received them from the laboratory 36. Given that the most cited potential barrier to ART adherence in this current study was time inconvenience, we hypothesise that this factor contributed to women delaying clinic attendance for their follow-up visits.…”
Section: Discussionmentioning
confidence: 88%